Cardiovascular risk factors and carotid intima media thickness in young adults born small for gestational age after cessation of growth hormone treatment: a 5-year longitudinal study. Issue 12 (December 2017) - van der Steen, Manouk; Kerkhof, Gerthe F; Smeets, Carolina C J; Hokken-Koelega, Anita C S
Summary: Background: Growth hormone treatment reduces blood pressure and lipid concentrations. We assessed long-term changes in blood pressure, lipid concentrations, and carotid intima media thickness over a 5-year period after cessation of growth hormone treatment in adults born small for gestational age. Methods: We did a longitudinal observational study at a medical centre in the Netherlands between April 1, 2004, and April 1, 2016. We included adults born small for gestational age who were treated with growth hormone (1 mg/m 2 per day); treatment started during childhood until adult height. Participants were evaluated at cessation of treatment, and 6 months, 2 years, and 5 years later. We compared cardiovascular risk factors with untreated controls from the PROGRAM study. Findings: We included 199 participants born small for gestational age and treated with growth hormone along with 285 controls: 51 untreated short adults born small for gestational age, 92 untreated adults born small for gestational age with spontaneous catch-up growth, and 142 adults born appropriate for gestational age. In the 6 months after treatment cessation, systolic blood pressure increased temporarily from 113·00 mm Hg (95% CI 111·18–114·82) to 116·92 mm Hg (115·07 to 118·77; p<0·001) and diastolic blood pressure increased temporarily from 62·19 mm Hg (60·99–63·38) to 66·51 mm Hg (65·14–67·89; p<0·001). At 5 years after treatment cessation, mean systolic blood pressure was 109·2 mm Hg (105·5–113·0) and mean diastolic blood pressure was 63·4 mm Hg (60·9–65·9), similar to the values at cessation. Lipid concentrations were non-significantly higher 5 years after treatment cessation (p values 0·09–0·21) than at treatment cessation. Cessation of growth hormone had no effect on carotid intima media thickness. At 5 years after cessation, total cholesterol was lower in adults treated with growth hormone (mean 4·21 mmol/L, 95% CI 4·04–4·38) than in untreated short adults born small for gestational age (4·66 mmol/L, 4·42–4·92; p=0·0030), as was mean LDL cholesterol (2·28 mmol/L, 2·14–2·43 vs 2·85 mmol/L, 2·62–3·10; p<0·0001); blood pressure and carotid intima media thickness did not differ between these two groups (p values >0·12). At 5 years after cessation, systolic blood pressure, diastolic blood pressure, lipid concentrations, and carotid intima media thickness of adults treated with growth hormone were not different to those in adults born small for gestational age who had spontaneous catch-up growth or adults born appropriate for gestational age. Interpretation: Long-term growth hormone treatment in children born small for gestational age has no unfavourable effects on cardiovascular health in early adulthood and improves lipid profiles. Funding: Novo Nordisk (Netherlands).